2018
DOI: 10.12816/0043492
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Inguinal Hernia among Children

Abstract: The aim of this study was to document clinical features of inguinal hernia (IH) in the pediatric populace. It delivers data to assess related risk factors of incarcerated hernia, its reappearance in addition to the occurrence of contra lateral metachronous hernia. Materials and Methods: We report a retrospective analytic study comprising 230 children presenting with IH and operated from April 2015 to June 2017 in the pediatric surgery department, King Abdulaziz Hospital. Results: We managed 36 girls (15.6%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Our study, unlike most others in the literature, found no significant difference in the occurrence of hernia in terms of location, with a right-to left-side ratio of 1.07:1. [5][6][7][8]16,18 There was 10.6% bilaterality of hernia, which is similar to reports in studies by Himanshu Acharya et al and Ezomike et al, 7,13 and lower than that reported in a study by Alrzoq et al 16 Among all patients, 28.8% (30/104) of cases presented with a hernia complication which required emergency surgery. Therefore, the overall incarcerations and strangulation rates in our study were 24% and 3.8%, respectively.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our study, unlike most others in the literature, found no significant difference in the occurrence of hernia in terms of location, with a right-to left-side ratio of 1.07:1. [5][6][7][8]16,18 There was 10.6% bilaterality of hernia, which is similar to reports in studies by Himanshu Acharya et al and Ezomike et al, 7,13 and lower than that reported in a study by Alrzoq et al 16 Among all patients, 28.8% (30/104) of cases presented with a hernia complication which required emergency surgery. Therefore, the overall incarcerations and strangulation rates in our study were 24% and 3.8%, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…This is a known fact and consistent with other similar studies. 5,7,8,13,16,17 Among all patients, infants less than one year of age accounted for about 58.7% (n=61) of the cases, which is a higher proportion than reported in other countries. 5,6,18 The age range at presentation varied from 1 day to 12 years, with a mean age of 15 months, which is lower than the mean ages reported in other studies.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Hernias are common in children and required various measures of treatment than an adult. It can occur due to weakness in the muscles of the abdomen in which part of the intestine may push through the weak area (Alrzoq, Alhaji & Alolayt, 2018). N a u s e a a n d v o m i t i n g a r e p o s t o p e r a t i v e gastrointestinal problems that may occur after operation and administration of anesthesia.…”
Section: Introductionmentioning
confidence: 99%